Blockade of endothelin-1 receptor B regulates molecules of the major histocompatibility complex in sickle cell disease - Inostroza-Nieves, Yaritza; Rivera, Alicia; Romero, José R. (Frontiers in Immunology, 2023)
Major Histocompatibility Complex (MHC) molecules have been proposed to play a role in Sickle Cell Disease (SCD) pathophysiology. Endothelial cells express MHC molecules following exposure to cytokines. SCD is characterized, in part, by vascular endothelial cell activation, increased oxidative stress, sickle cell adhesion, and excess levels of endothelin-1 (ET-1) contributing to vaso-occlusive crises. ET-1 activates endothelial cells, induces oxidative stress and inflammation, and alters erythrocyte volume homeostasis. However, the role of ET-1 on MHC regulation in SCD is unclear. We first studied two sickle transgenic knockout mouse models of moderate to severe disease phenotype, βS-Antilles and Berkeley (BERK) mice. We observed significant increases in H2-Aa mRNA levels in spleens, lungs, and kidneys from transgenic sickle mice when compared to transgenic knockout mice expressing human hemoglobin A (HbA). Mice treated for 14 days with ET-1 receptor antagonists significantly reduced H2-Aa mRNA levels. We characterized the effect of ET-1 on MHC class II expression in the human endothelial cell line EA.hy926. We observed dose-dependent increases in the expression of MHC class II (HLA-DRA) and MHC transcription factor (CIITA) that were significantly blocked by treatment with BQ788, a selective blocker of ET-1 type B receptors. Chromatin immunoprecipitation studies in EA.hy926 cells showed that ET-1 increased Histone H3 acetylation of the HLA-DRA promoter, an event blocked by BQ788 treatment. These results implicate ET-1 as a novel regulator of MHC class II molecules and suggest that ET-1 receptor blockade represents a promising therapeutic approach to regulate both immune and vascular responses in SCD.